Educational Game in Learning Arabic Language for Modern Islamic Boarding School - Hasna Azizah; Fatah Yasin Irsyadi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Modern Islamic Boarding Schools began to implement the 2013 Curriculum without overriding the cottage materials sourced from Kitab. The Kitab used is written in Arabic. Even some Kitab are written without harakat, or commonly called bald Arab. Therefore, students have demands to memorize a lot of mufrodat (Arabic vocabulary) and have a heavier learning burden. Arabic is the key to understanding students in the matter of the lodge. Though the learning process is carried out conventionally and theoretically without interesting learning media. The purpose of making educational games in learning Arabic that is adapted to the Arabic curriculum is so that students can balance K13-based learning with teaching processes that are more effective, efficient, and enjoyable. Researchers chose Grade VII students as users in this educational game because they are the first level in the junior high school unit and to increase the attractiveness of students in learning Arabic. The application creation process uses Construct 2 software, Adobe Illustrator 2019 and Adobe Photoshop CS6. The results of this study, based on the results of User Acceptance Testing (UAT) show the average value of interpretation or user ratings of 89.92% which shows that the level of acceptance of respondents in the category of “Strongly Agree”. The application can help students in memorizing mufrodat shown with an average percentage of 95.2%. This result is supported by the research instrument in 9 questions about valid and reliable questionnaires that were tested using IBM SPSS Statistics 25 software.